Análisis de mercadeo y comercialización en la cadena de valor de maní arachis hypogaea l., en la provincia de Loja - Jiménez Guayanay, Teresa Alexandra (2021)
Peanuts are the third most produced legume in the world, despite the information generated, there is a gap in aspects of marketing activities, actors and their price formation in marketing. The present investigation had as objectives: to characterize the marketing activities; analyze the components of the marketing channels and a population sample of 309 producers was obtained, distributed in each of the study sectors, where the survey was applied. The research was carried out in the parishes of San Antonio, Yamana, Casanga, Bramaderos, Las Cochas and San Vicente del Río, of the Paltas canton; the Buenavista and Santa Rufina de Chaguarpamba parishes; the La Tingue parish belonging to Olmedo and the parishes 27 de Abril, El Ingenio de Espíndola, in the province of Loja, in addition, interviews and surveys were conducted with merchants and processors. To represent the results, the GraphPad Prism 8 software, infostat, processing cost matrix, the Michael Porter model was used. As results, it was identified that, in the marketing activities, there is natural drying, mechanical shelling predominates, purity analyzes are not carried out, nor are moisture percentages determined for commercialization by the producer, however, in the elaborated analysis From the grain, the 8.2% humidity percentage was obtained, which is optimal for commercialization, while the 96.7% purity is low for commercialization. In marketing, the producers sell the product in the cantonal capitals. Regarding the case studies for the industrial production of peanut paste, if there is the recovery of the benefit of the total investment cost, for the sale of a unit produced, on the other hand, for the manufacture of the sandwich it does not contain any benefit. Within the chain of actors in marketing, the most representative of the sectors is: producer, wholesaler, retailer, consumer, with a decrease in the tendency to use it directly. For the formation of the price for the purchase of 45 kg of peanuts, there is a higher profitability of profit, at the level of intermediaries and the producer is the one with the lowest percentage of economic profit. Keywords: marketing, value chain, price formatio